PENGARUH ARUS KAS DAN MODAL KERJA TERHADAP PROFITABILITAS PADA KOPERASI SIMPAN PINJAM MAKMUR MANDIRI DI SURABAYA - Rina Wati (ECONOMOS, 2022)
Assets in the company in the form of cash is a very important variable for the company, then one way to maximize profits from the operational side is the need for working capital management. This study aims to determine and analyze the effect of cash flow and working capital on profitability at the Makmur Mandiri Savings and Loans Cooperative in Surabaya. This research method is explanatory research using quantitative research. The sample used in this study is data from 5-year cooperative financial statements, namely from 2016 to 2020, the source of data used in this study is secondary data. Data analysis using multiple linear regression analysis and hypothesis testing, with SPSS data processing. The results of the study conclude that there is a significant effect of cash flow on profitability at the Makmur Mandiri Savings and Loans Cooperative in Surabaya, and there is a significant effect of working capital on the profitability of the Makmur Mandiri Savings and Loans Cooperative in Surabaya.